2022
DOI: 10.1111/jfpe.14038
|View full text |Cite
|
Sign up to set email alerts
|

Solar energy‐based extraction of essential oils from cloves, cinnamon, orange, lemon, eucalyptus, and cardamom: A clean energy technology for green extraction

Abstract: Conventional essential oil extraction systems cannot meet the green extraction concepts and sustainable development goals (SDGs). Therefore, there is a need to develop alternative systems based on clean energy. The present study aims to investigate the possibility of essential oil extraction using solar energy without utilizing synthetic solvents. Hence, an eco-friendly solar energy-based extraction system (SEE) was developed to extract essential oils from cloves and cinnamon barks, orange and lemon peels, euc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…SEE when compared to traditional hydrodistillation, extraction time was increased by 0.45 h with an optimized solar radiation of about 1000 W/m 2 . Further analysis revealed that SEE was 23-34% greener than the traditional hydrodistillation based on plant material type (9).…”
Section: Advance Extraction Techniquesmentioning
confidence: 90%
See 3 more Smart Citations
“…SEE when compared to traditional hydrodistillation, extraction time was increased by 0.45 h with an optimized solar radiation of about 1000 W/m 2 . Further analysis revealed that SEE was 23-34% greener than the traditional hydrodistillation based on plant material type (9).…”
Section: Advance Extraction Techniquesmentioning
confidence: 90%
“…Various extraction procedures have been used to obtain phytochemicals, and can be classified as conventional-(e.g., hydrodistillation, steam distillation and Soxhlet extraction) and advance extraction methods (e.g., enzyme-assisted-, instant controlled pressure drop-, microwave-assisted-, pressurized liquid-, solar energy-based-, sub-critical-, supercritical fluid-, and ultrasound-assisted extractions) (2,9,10,(20)(21)(22)(23)(24)(25). Conventional extraction methods have wider applicability in the extraction of phytochemicals due to ease of operation, however, they require more time and huge amount of solvents, and give less extraction yield, thus making up-scaling difficult.…”
Section: Phytochemicals Extraction Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oils from different plant sources are extracted using a solar distillation system like eucalyptus leaves, peppermint leaves, clove buds, fennel seeds, basil, lavender, cumin, cardamom, orange, lemon, rosemary, citrus, Cymbopogon, etc. (Table 8) (Al-Hilphy et al, 2022;Radwan et al, 2020;Afzal et al, 2017;Yen and Lin, 2017). Antioxidant and antimicrobial activity (Afzal et al, 2017;Schmidt et al, 2009;Mimica-Dukić et al, 2003) Pinus (Roxburghii) α-Pinene (Afzal et al, 2017) Lavandula angustifolia; Lamiaceae (Flowers) Lavender β-Pinene, β-phellandrene, borneol, camphor, linalool, terpineol, linalyl acetate, terpineol-4-ol, cymene and 1,8-cineole Antimicrobial, anti-inflammatory, and antioxidant activity (Radwan et al, 2020;Lakušić et al, 2014;Danh et al, 2012;Wells et al, 2018) Cymbopogon citratus (DC) Stapf..; Poaceae (Leaves)…”
Section: Ohmic Heated Water Distillationmentioning
confidence: 99%